Behavioral Factors Affecting Patient's Compliance in Consuming Anti-diabetic Oral Drugs - Liza Pristianty (Journal of Global Pharma Technology, 2016)
Introduction: Treatment compliance is a major problem in overcoming diabetes mellitus. This case inhibits the achievement of optimal levels of health for people with diabetes mellitus. However, various types of factors that enable patients to be disobedient to treatment have not been widely studied in terms of pharmacy. Objective: This study aimed to identify behavioral factors that influence diabetes mellitus patient compliance in taking oral antidiabetic drugs. Methods: This study was observational analysis using cross-sectional design. Sampling was obtained by accidental sampling method. The independent variables in this study were the knowledge and attitudes of patients; availability of health care facilities, and behavior of pharmaceutical officers. Whereas, the dependent variable was the compliance of the patients with diabetes mellitus taking antidiabetic drugs. Data were collected using valid questionnaires then analyzed using correlational analysis. Results: The results of this study indicated that the support of pharmacists had significant effect on patient compliance (p = 0.006). Whereas, knowledge, behavior, and availability of health service facilities had no significant effect on patient compliance in taking oral antidiabetic drugs (results in sequence: p = 0.642; p = 0.379; p = 0498). Conclusion: The role of pharmacist is very important in efforts to provide information and motivation for the treatment of diabetes mellitus, especially the consumption of oral antidiabetic drugs. This research is expected to improve pharmacy services related to the accuracy of providing information to patients. It will also have an impact on improving the quality of life of patients and providing quality services.Keywords: Behavioral factors, Diabetes mellitus, Patient compliance.